Gene Expression Analysis for Drought Tolerance in Early Stage of Potato Plant Development - Rakhim Kanat; Malika Shamekova; Zagipa Sapakhova; Maxat Toishimanov; Dias Daurov; Nurgul Raissova; Zhanar Abilda; Ainash Daurova; Kabyl Zhambakin (Biology)
Drought has increasingly affected the yield of Solanum tuberosum L. (potato) every year over the last decade, posing serious economic problems for the global agricultural industry. Therefore, it is important to research drought tolerance in plants and obtain more robust varieties of crops. The aim of the present work was to study the expression of drought-upregulated genes in drought-tolerant and drought-sensitive varieties of potato. Bioreactors were used to identify whether each variety was drought-tolerant or drought-sensitive; then, expression analysis was performed according to the morphological characteristics of the plantlets in two different media: Murashige and Skoog (MS) medium and MS medium with 20% PEG-6000 to simulate osmotic stress. Based on the quantitative parameters of six initial varieties, two varieties were selected (Gala and Aksor) for further gene expression analysis. The expression of genes commonly upregulated in drought (ER24, TAS14, DREB147315, PP2C, 102605413 and NF-YC4) was higher in the drought-tolerant variety than in the sensitive one. Therefore, the expression of these genes can be used to determine the drought tolerance of a potato variety in vitro in the early plant development stage. Moreover, comparative analysis showed that some of the targeted genes used to identify drought tolerance in this study are conserved across different plant species.